AB0185 Clinical joint involvement is decisive for radiographic progression. (23rd January 2014) - Gärtner, M.; Alasti, F.; Supp, G.; Smolen, J.; Aletaha, D.
Abstract : Background: Today's therapeutic targets in rheumatoid arthritis (RA) are remission or low disease activity, but it was shown that joint damage may continue to progress despite these favourable clinical states. 1 ;2 While progression of joint damage is related to joint swelling, 3 ;4 radiographic damage may progress even without evidence of clinical synovitis, at least in early RA. 5 Objectives: To evaluate the frequency of radiographic progression in clinically persistently inactive joints of patients with established RA. Methods: We included 80 random RA patients (mean disease duration: 7.32±9.78 yrs.) with radiographic progression (increase≥1) by the Sharp van der Heijde (SvdH) score over an observational period of at least three to a maximum five years. To conform with the records of clinical joint assessment, we only considered radiographic progression in any of the 22 hand/finger joints (10 proximal interphalangeal joints[PIP], 10 metacarpophalangeal joints[MCP], and the 2 wrists), but excluded the feet (not assessed by the 28 joint count). Clinical data on individual joints (swelling and tenderness) from each clinical visit performed between one year prior to the baseline x-ray until the time of the x-ray endpoint were collected from the patient charts. We evaluated whether there are joints showing radiographic progression despite clinical inactivity and compared them to progressing joints that were clinically active. Further, patients with radiographic progression in clinically inactive joints were compared to those with clinical activity. Results: The mean±SD time between x-rays was 3.51±0.41 yrs and the mean number of clinical visits per patient was 16.3±4.32. A total of 104 (5.9%) of the 1760 evaluated joints showed progression in erosions and 206 (12.8%) worsened in joint space narrowing (JSN). Of all joints with progression in erosions, 30 (28.8%) were never swollen during the observation period (in 19 patients), 16 (53.3%) were never swollen in the total patient history, and only 7 (6.7%) never showed any activity also by tenderness. In the total patient population, progression was higher in joints with clinical swelling (during the observation period) compared to joints without swelling (2.36±1.7 vs 1.76±1.62). The number of visits with swelling correlated to a low but significant extent with the rate of radiographic progression (r=0.13; p<0.01). The overall sensitivity for progression of damage of any joint activity during the observation period was 78.8% for erosion, and 77.7% for JSN. Sensitivity increased to >90% when including ever clinically active joints since onset of disease. Conclusions: Only 7% of joints with radiographic progression in patients with established RA show consistent lack of clinical activity, and these joints show a low degree of progression. Thus, radiographic progression despite lacking clinical activity is a negligible event on the joint level. Clinical joint involvement is decisive for progression of joint damage and continues to be a highly predictive outcome measure for monitoring patients with RA. References: Aletaha D et al. Arthritis Rheum 2009; 60(5):1242-1249. Molenaar ET et al. Arthritis Rheum 2004; 50(1):36-42. Aletaha D et al. Ann Rheum Dis 2011; 70(11):1975-1980. van Riel PL et al. J Rheumatol 1995; 22(9):1797-1799. Klarenbeek NB et al. Ann Rheum Dis 2010; 69(12):2107-2113. Disclosure of Interest: None Declared